Using gamification as a teaching tool to manage EFL learners' speaking anxiety - Lin, Ziyi (2023)
Gamification can be applied to the field of language education. This study explored the feasibility of using gamification to alleviate EFL students' speaking anxiety in the foreign language classroom by using a mixed quantitative and qualitative approach. The study used McCroskey's (2005) Personal Report of Communication Apprehension (PRCA) as the survey text for the questionnaire, which was collected from a sample of 60 Chinese students from UTAR Kampar. Based on the results of the questionnaire, the speaking anxiety levels of the60 students in four different scenarios were calculated. For the qualitative study, six students with the highest anxiety levels in the questionnaire were selected for experimental and semi-structured interviews. The findings showed that most of the participants recognized the effectiveness of using gamification to alleviate speaking anxiety and felt that this approach allowed them to learn more authentic vocabulary. At the end of the research, the researcher points out suggestions for future research in the field of gamification and the feasibility of teachers using gamification for language teaching